SYMBOLIC GOVERNANCE OR LEGAL ACCOUNTABILITY? RETHINKING ADIPURA IN INDONESIA’S ENVIRONMENTAL GOVERNANCE REGIME: A Socio-Legal Analysis - Tyasning Permanasari; Suparto Wijoyo; Mas Rahmah; Radian Salman (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2026)
This study examines the Adipura Program within Indonesia’s decentralized environmental governance system by addressing the gap between legal norms and administrative practices. Although Indonesia has established a comprehensive environmental legal framework, the implementation of environmental governance instruments often remains symbolic rather than transformative. This research aims to analyze the juridical status and effectiveness of the Adipura Program and to propose a socio-legal reconstruction to strengthen environmental accountability. The study employs a socio-legal approach that integrates normative legal analysis with governance analysis. The data consist of statutory regulations, policy documents, and environmental governance reports, which are analyzed using Friedman’s legal effectiveness theory and Kooiman’s interactive governance framework. The findings reveal that Adipura primarily functions as a recognition-based administrative mechanism with limited binding legal authority, fragmented institutional coordination, and weak participatory accountability. Evaluation indicators tend to emphasize visible environmental outputs rather than institutional governance capacity. The study proposes a reconstruction model based on three key dimensions: strengthening statutory legal foundations, integrating environmental indicators into public sector accountability systems, and expanding participatory governance mechanisms. Theoretically, this study contributes to socio-legal environmental governance scholarship by showing how recognition-based environmental instruments may lose legal effectiveness when legal substance, institutional structure, and governance culture are not coherently aligned. This research contributes to environmental governance scholarship by repositioning Adipura as a legal governance instrument and advancing socio-legal analysis of environmental policy instruments in decentralized systems.